2016
DOI: 10.1007/s12328-016-0648-5
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hepatitis following drug-induced liver injury in an elderly patient

Abstract: We describe a case of autoimmune hepatitis (AIH) that may have occurred following drug-induced liver injury with camostat mesilate and/or benzbromarone in an elderly patient. The patient's liver biopsy showed chronic active hepatitis and autoimmune hepatitis. Stopping the use of these drugs did not lead to complete remission, but the use of a low dose of corticosteroids completely cured his liver dysfunction. In the present case, liver dysfunction was caused by an autoimmune mechanism. Special attention should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In a second scenario, an episode of DILI/HDS triggers chronic AIH. This constellation has been proposed by case reports [ 55 ]. However, causality between drug intake and manifestation of chronic AIH cannot be proven thus far.…”
Section: Clinical Context Of Drug-induced Liver Injury and Hepaticmentioning
confidence: 89%
“…In a second scenario, an episode of DILI/HDS triggers chronic AIH. This constellation has been proposed by case reports [ 55 ]. However, causality between drug intake and manifestation of chronic AIH cannot be proven thus far.…”
Section: Clinical Context Of Drug-induced Liver Injury and Hepaticmentioning
confidence: 89%
“…In this report, while possible, benzbromarone toxicity remains questionable, especially in light of the probable causal role of the co-administered camostat mesilate, which had demonstrated a positive lymphocyte stimulation test, in contrast to benzbromarone. However, it was not possible to entirely rule out benzbromarone [36].…”
Section: Discussionmentioning
confidence: 99%
“…In our literature review, we found no published reports on this topic in the Latin American databases Lilacs and SciELO. Our search found only one additional report, which was published in 2016 in Japan [36]. A total of 11 cases of hepatotoxicity related to benzbromarone were reported by the Periodic Safety Update Report (PSUR) between 1995 and 2000.…”
Section: Safety Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Autoimmune hepatitis (AIH) and primary biliary cholangitis (PBC) are representative autoimmune liver diseases [ 4 , 5 ]. AIH possesses a chronic active hepatitis histologically with autoimmune features and poor prognosis without immune suppressive therapies [ 4 , 6 ]. PBC is diagnosed based on the presence of an antimitochondrial antibody (AMA), elevated cholestatic liver enzyme and/or histologically by chronic non-suppurative destructive cholangitis (CNSDC) [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%